Estimation of occupational safety risks at energetic sector of Iron and Steel Works - Kukhar, Volodymyr; Yelistratova, Nelly; Burko, Vadym; Nizhelska, Yulia; Aksionova, Olga (International Journal of Engineering and Technology, 2018)
Modern methods of estimation of working conditions at the metallurgical enterprise are considered on the occupational safety due to European standards. The main approaches are identified in determination of hazards at work, assessing of technological risks and injuries as an example for one of the Iron and Steel Works,Mariupol,Ukraine. The purpose of this work is to analyze the effectiveness of the introduction of international methods in the field of health safety, assess the effectiveness of the safety management system at an industrial enterprise. The analysis of the process of implementing European standards in the field of the health safety at industrial enterprises is a prerequisite for their further successful application, reducing the level of injuries. The procedures for drawing up the matrix of risk assessment (HAZID method), assessment of working capacity of technological processes (HAZOP method), and safety assessment of works (ISA method) are considered. The analysis of the efficiency of measures to increase of health safety in the energy (gas) sector at the enterprise was carried out. A graph of the dynamics of the decline in industrial injuries in five years is shown. The main statistical indicators that are used to account for industrial injuries at an industrial enterprise are given.Â